A congenital wandering spleen with a large epithelial cyst: A case report - Youhok Lim; Hour Leng; Chi Hoon Lee; Vireak Chhun; Young Don Lee (Clinical Case Reports, 2022)
Abstract We present a case of a 21‐year‐old female patient who had a wandering spleen with a large cyst. The celiotomy was performed under the impression of torsion of the wandering spleen and leakage from the splenic cyst. The total splenectomy was performed instead of cystectomy and splenopexy.